2011
DOI: 10.2223/jped.2145
|View full text |Cite
|
Sign up to set email alerts
|

Bubble CPAP versus CPAP with variable flow in newborns with respiratory distress: a randomized controlled trial

Abstract: Objective: To evaluate the efficacy and safety of nasal continuous positive airway pressure (NCPAP) using devices with variable flow or bubble continuous positive airway pressure (CPAP) regarding CPAP failure, presence of air leaks, total CPAP and oxygen time, and length of intensive care unit and hospital stay in neonates with moderate respiratory distress (RD) and birth weight (BW) ≥ 1,500 g. Methods:Forty newborns requiring NCPAP were randomized into two study groups: variable flow group (VF) and continuous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 16 publications
(26 reference statements)
0
26
0
7
Order By: Relevance
“…24 No differences were reported between the therapies for outcome measures of percentage CPAP failure, percentage barotrauma, duration of CPAP use, duration of oxygen use, ICU stay, and hospital stay. The findings suggest that the physiologic effect of the pressure oscillations from bubble CPAP is less prevalent as the lungs mature.…”
Section: Discussionmentioning
confidence: 96%
“…24 No differences were reported between the therapies for outcome measures of percentage CPAP failure, percentage barotrauma, duration of CPAP use, duration of oxygen use, ICU stay, and hospital stay. The findings suggest that the physiologic effect of the pressure oscillations from bubble CPAP is less prevalent as the lungs mature.…”
Section: Discussionmentioning
confidence: 96%
“…[8][9][10] Others have found no differences in clinical outcomes or physiological parameters. 11,19 Yagui et al 19 reported a similar CPAP failure rate by 72 h of life between variable flow Bober et al 13 reported a multicenter RCT from Poland comparing IFD with constant flow CPAP using ventilator in preterm infants ⩽ 32 weeks and birth weight of 750 to 1500 g in both primary treatment for RDS as well as post-extubation settings. Even though a combined analysis did not reveal any differences in the need for intubation, in the post-extubation setting, IFD had significantly lower failure rates but paradoxically higher rates of pneumothorax.…”
Section: Discussionmentioning
confidence: 97%
“…Small RCTs or crossover studies have compared Infant Flow Driver (IFD) to B-CPAP or ventilator (V-CPAP) for primary treatment of RDS. [8][9][10][11]19 Some authors have shown a 13 to 29% reduction in work of breathing, a better lung compliance at a pressure range of 4 to 7 cm H 2 0 and lesser oxygen requirements with IFD when compared with constant flow CPAP. [8][9][10] Others have found no differences in clinical outcomes or physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…17 Oksijen doygunluğu %88-94 arasında olacak şe-kilde (PEEP, FiO 2 ) ayarlamalarının yapılması gereklidir. 1 Bebekte burun yaralanması, nekrozu ve kanama gibi komplikasyonları önlemek için gerekli önlemler alınmalıdır. Her bebek için doğru boyutta kanül/maske seçilmeli, bebeğin burnuna kanül veya maske yerleştirmeden önce baş 30˚yükseltil-meli, omuzlar rulo ile desteklenerek başa koklama pozisyonu verilmelidir.…”
Section: Hemşi̇reli̇k Bakimiunclassified